2015
DOI: 10.1007/s40616-015-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Prompting Tactics for Teaching Intraverbals to Young Adults with Autism

Abstract: Several researchers have compared the effectiveness of tact or textual prompts to echoic prompts for teaching intraverbal behavior to young children with autism. We extended this line of research by comparing the effectiveness of visual (textual or tact) prompts to echoic prompts to teach intraverbal responses to three young adults with autism. An adapted alternating treatments design was used with 2 to 3 comparisons for each participant. The results were mixed and did not reveal a more effective prompting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
3
16
0
3
Order By: Relevance
“…and poses a harder challenge for many children with autism and other cases of developmental disabilities due to the lack of point-to-point correspondence be- In some of the mentioned studies, a textual prompt was used besides a tact or echoic prompt like Braam and Poling (1983), Emmick, Cihon and Eschleman (2010), Finkel and Williams (2001), , Vedora and Conant (2015), Vedora, Meunier and Mackay (2009). According to Skinner (1957), the textual behavior occurs when, for example, an adult presents a flashcard with a printed word "cookie" on it and a child says "cookie" out loud.…”
Section: The Applied Behavior Analysis As a Possibility Ofmentioning
confidence: 99%
“…and poses a harder challenge for many children with autism and other cases of developmental disabilities due to the lack of point-to-point correspondence be- In some of the mentioned studies, a textual prompt was used besides a tact or echoic prompt like Braam and Poling (1983), Emmick, Cihon and Eschleman (2010), Finkel and Williams (2001), , Vedora and Conant (2015), Vedora, Meunier and Mackay (2009). According to Skinner (1957), the textual behavior occurs when, for example, an adult presents a flashcard with a printed word "cookie" on it and a child says "cookie" out loud.…”
Section: The Applied Behavior Analysis As a Possibility Ofmentioning
confidence: 99%
“…Several studies have shown that tact, textual (visual), and echoic (vocal) prompts may be used to transfer control to verbal stimuli when teaching intraverbals to children with and without developmental disabilities (e.g., Goldsmith, LeBlanc, & Sautter, 2007;Ingvarsson, Tiger, Hanley, & Stephenson, 2007;Miguel, Petursdottir, & Carr, 2005;Valentino, Shillingsburg, & Call, 2012). The few studies comparing prompt topographies (Finkel & Williams, 2001;Ingvarsson & Hollobaugh, 2011;Ingvarsson, & Le, 2011;Vedora, Meunier, & Mackay, 2009;Vedora & Conant, 2015;Wallace, Bechtel, Heatter, & Barry, 2016) have found that the most effective and efficient prompt varied across participants. Some authors hypothesized that the success of a specific prompt may depend on an individual's learning history (Finkel & Williams, 2001;Ingvarsson & Hollobaugh, 2011).…”
mentioning
confidence: 99%
“…On the one hand, if studies with the teaching of echoic as the main objective seem to be scarce; on the other hand, there are many studies that use the echoic as a prompt for the acquisition of other operators such as tact, mand and intraverbal (Carroll & Kodak, 2015;Smith et al, 2016;Vedora & Conant, 2015;Williams, Carnerero, & Peréz-Gonzalez, 2006). In such cases, the procedures may involve vocal presentation of the desired verbal response, with differential reinforcement (modeling) and fading of the echoic prompt (by remission of phonemes or delay).…”
Section: Introductionmentioning
confidence: 99%